Clubfoot treatment with Ponseti method: parental distress during plaster casting - Walter, Christian; Sachsenmaier, Saskia; Wünschel, Markus; Teufel, Martin; Götze, Marco (Journal of orthopaedic surgery and research, 2020)
Clubfoot is one of the most prevalent musculoskeletal congenital defects. Gold standard treatment of idiopathic clubfoot is the conservative Ponseti method, including the reduction of deformity with weekly serial plaster casting and percutaneous Achilles tenotomy. It is well known that parents of children with severe and chronic illnesses are mentally stressed, but in recent studies regarding clubfoot treatment, parents were only asked about their satisfaction with the treatment. Largely unknown is parental distress before and during plaster casting in clubfoot.